Immobilization of Purified Pectin Lyase from Acinetobacter calcoaceticus onto Magnetic Carboxymethyl Cellulose Nanoparticles and Its Usability in Food Industry - Esen Tasgin; Aynur Babagil; Hayrunnisa Nadaroglu (Journal of Chemistry)
An important component of the pectinase enzyme complex is pectin lyase (polymethylgalacturonate lyase; EC 4.2.2.10). In this study, extracellular pectin lyase enzyme was produced from Acinetobacter calcoaceticus bacteria. Pectin lyase was then purified using three-phase precipitation (TPP) technique with 25.5% yield. The pectin lyase was immobilized covalently via the L-glutaraldehyde spacer to the carboxymethyl cellulose. The immobilized pectin lyase was magnetized using Fe3O4 nanoparticles. Purified pectin lyase was connected to magnetized support material after 90 min at the rate of 80%. The most appropriate immobilization conditions were determined as pH 8 and 30°C. By characterizing the free and immobilized enzyme, KM, Vmax, and optimum pH and optimum temperature values were determined. It was optimum pH 8 and temperature 50°C for both free and immobilized pectin lyase. The structural characterization of the immobilized pectin lyase modified with Fe3O4 nanoparticles was carried out by SEM, FT-IR, and XRD chromatographic analyses. At the end of the study, free and immobilized enzymes were used for purification of some fruit juices and results were compared.